Bone transport combined with sequential nailing technique for the management of large segmental bone defects after trauma - Wang, Qian; Ma, Teng; Li, Zhong; Zhang, Kun; Huang, Qiang (Frontiers in Surgery, 2024)
Background: Bone transport technique is widely used for the management of large segmental bone defects. However, several reasons may prevent its successful completion, such as poor osteogenesis, docking site nonunion, severe chronic pain and psychological problems. We used sequential nailing technique to solve these problems. The objective of this study was to analyze the clinical effects of our modified technique for the management of large segmental bone defects after trauma. Methods: Twenty-three patients using bone transport combined with sequential nailing technique in our institution from June 2011 to June 2020 were included and analyzed retrospectively. There were 15 males and eight females. The age ranged from 19 to 64 years. There were eight cases suffering from basic medical diseases. The initial injury was open in 14 patients. Seven cases encountered femoral defects and 16 for tibia. The main reasons for sequential nailing technique were docking site nonunion (nine cases), poor osteogenesis (five cases), severe chronic pain (five cases) and psychological problems (four cases). The residual bone defects after removing the external fixator, operation plans, complications and follow-up time were recorded. Bone defect healing was evaluated by Paley score. Results: The mean residual bone defects were (2.9±1.9) cm. The mean time in external fixator was (9.5±3.4) months. The average follow-up time was (23±3) months. With respect to complications, two cases suffered from nonunion again and were treated by bone graft with augmented plate fixation. No infection recurrence was found in these cases. The excellent and good rate of bone defect healing was 91.3%. Conclusion: Bone transport combined with sequential nailing technique could shorten the external fixation time, overcome the inconvenience of the external frame to patients, eliminate chronic pain and be easy for patients to accept. Patients using this modified technique achieved high satisfaction.